Wheat NAC transcription factor NAC5‐1 is a positive regulator of senescence - Catherine Evans; Sophie Louise Mogg; Charline Soraru; Emma Wallington; Juliet Coates; Philippa Borrill (Plant Direct)
Abstract Wheat (Triticum aestivum L.) is an important source of both calories and protein in global diets, but there is a trade‐off between grain yield and protein content. The timing of leaf senescence could mediate this trade‐off as it is associated with both declines in photosynthesis and nitrogen remobilization from leaves to grain. NAC transcription factors play key roles in regulating senescence timing. In rice, OsNAC5 expression is correlated with increased protein content and upregulated in senescing leaves, but the role of the wheat ortholog in senescence had not been characterized. We verified that NAC5‐1 is the ortholog of OsNAC5 and that it is expressed in senescing flag leaves in wheat. To characterize NAC5‐1, we combined missense mutations in NAC5‐A1 and NAC5‐B1 from a TILLING mutant population and overexpressed NAC5‐A1 in wheat. Mutation in NAC5‐1 was associated with delayed onset of flag leaf senescence, while overexpression of NAC5‐A1 was associated with slightly earlier onset of leaf senescence. DAP‐seq was performed to locate transcription factor binding sites of NAC5‐1. Analysis of DAP‐seq and comparison with other studies identified putative downstream target genes of NAC5‐1 which could be associated with senescence. This work showed that NAC5‐1 is a positive transcriptional regulator of leaf senescence in wheat. Further research is needed to test the effect of NAC5‐1 on yield and protein content in field trials, to assess the potential to exploit this senescence regulator to develop high‐yielding wheat while maintaining grain protein content.